Problems of career choice and personality traits - Pociūtė, B.; Isiūnaitė, V. (Psichologija, 2011)
Many young people are faced a certain amount of indecision related to making career choice. This study investigates how the personality traits are related to career indecision and what psychological factors impede the career choice. Data were collected twice, 4 months apart, to study the possible changes in decision status. For the autumn term, 200 participants were 10th-grade and 182 12th-grade students from two gymnasiums (in Jonava and Vilnius). For the spring term, 70 percent of participants were 12th-grade students and 84 percent 10th-grade students who filled in the questionnaires in the autumn term. The career indecision was assessed by the Career Decision Scale (Osipow et al., 1976), the personality traits by the Big Five Adjective Test (Gintilienė and Standikė, 2009; Zdanevičiūtė, 2003), and a 28-item scale was devised for assessing indecisiveness. The vocational choice questionnaire was constructed for assessing some psychological factors of vocational choice. The results of this study demonstrated no differences in career indecision according to grade level. The means of indecision significantly decreased over time only for 10th-grade students from Vilnius. Upon analyzing the difficulties in career decision-making, the conclusion was that the lack of information about the occupation, the self and about the ways of deciding was an obstacle. During the career decision making process, students with a serious level of indecision paid more attention to the external factors such as financial resources. Students with a low level of career indecision paid more attention to the internal factors such as a hobby. Within this sample, career indecision was positively and significantly related to such personality trait as indecisiveness (girls, r = 0.513, boys, r = 0.451; p < 0.01). Career indecision was found to be negatively related to emotional stability and extraversion for schoolgirls (respectively r = –0.253, r = –0.224; p < 0.01). Participants with a low level of indecision were found to be more decisive and emotionally stable as compared with the participants with a middle and a high levels of indecision, more extraverted and intellectual being the schoolgirls’ sample.
Keywords: career indecision; difficulties in career choice making; personality traits; indecisiveness